Reading and writing: still a challenge - Bergamin, Maria Estela (2007)
This report discusses the "Reading and Writing Project: a challenge for all," which is part of the School Territory Program (Programa Território Escola) developed by CENPEC in partnership with Fundação Volkswagen. The goal was to develop the capacity for reading and text production, in different knowledge areas, with students in grades 5 through 8. Activities started in São Carlos – SP, São Bernardo do Campo – SP and the Municipal School System of Bebedouro – SP, involving 131 schools and 408 educators, who took part in a systematic continuing education program over three years. As an example, the report offers a summary of the proposals drafted by CENPEC trainers and teachers in São Carlos in 2006. After a year and a half of work, the results showed that the teachers in every area included reading and writing in the content for their subject areas, which the proposal encompassed for the community, providing meaning to the search for knowledge, and there was a strengthening of the managers as articulators of the curriculum.